2020
DOI: 10.1007/s40544-019-0345-8
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance and microstructural evolution of α-brass alloys as a function of zinc concentration

Abstract: Tailoring a material's properties for low friction and little wear in a strategic fashion is a long-standing goal of materials tribology. Plastic deformation plays a major role when metals are employed in a sliding contact; therefore, the effects of stacking fault energy and mode of dislocation glide need to be elucidated. Here, we investigated how a decrease in the stacking fault energy affects friction, wear, and the ensuing sub-surface microstructure evolution. Brass samples with increasing zinc concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The SAGB identified in Fig. 4a has been described as a dislocation trace line (DTL) in earlier publications [4,5,13]. The DTL in CoCrFeMnNi will be further discussed in the subsection 'Dislocation trace line and crystal rotation'.…”
Section: Influence Of Initial Grain Orientationmentioning
confidence: 87%
See 2 more Smart Citations
“…The SAGB identified in Fig. 4a has been described as a dislocation trace line (DTL) in earlier publications [4,5,13]. The DTL in CoCrFeMnNi will be further discussed in the subsection 'Dislocation trace line and crystal rotation'.…”
Section: Influence Of Initial Grain Orientationmentioning
confidence: 87%
“…In essence, a tribological system features two forces controlling the microstructural evolution: first, the normal force, which can be easily adjusted and second, the friction force, which is a function of the tribological system itself. Further parameters determining the deformation layer are cycle number [4,13,14], sliding velocity [15,16], temperature [16] and ambient environment [17].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast was then referred to as the dislocation trace line (DTL). The occurrence of the DTL, which was also found in arrays of copper alloys and nickel [27,28], was explained through the motion of dislocations in the complex stress field associated with the moving sphere. It was recently observed that this dislocation self-organization is also the location where a localized simple shear of the subsurface material occurs in the sliding direction [24].…”
Section: Introductionmentioning
confidence: 87%
“…This work is further motivated by the evidence that ductile crystalline materials often exhibit deformed layers (termed as "tribo-layers" or "third body" [19]) arising from localized plasticity when subjecting to contact and tribological loads [20][21][22][23][24]. Simulations have been performed to understand the interaction between the contact and microstructural changes [13,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%